After Posterior Fusions for Adult Spinal Deformity, Operative Time is More Predictive of Perioperative Morbidity, Rather Than Surgical Invasiveness: A Need for Speed?. Issue 24 (15th December 2017) - Samuel, Andre M.; Fu, Michael C.; Anandasivam, Nidharshan S.; Webb, Matthew L.; Lukasiewicz, Adam M.; Kim, Han Jo; Grauer, Jonathan N.
Abstract : Study Design: A retrospective cohort study. Objective: The aim of this study was to determine the independent effects of operative time and surgical invasiveness on perioperative outcomes after posterior spinal fusions for adult spinal deformity. Summary of Background Data: Morbidity is high after posterior fusions for adult spinal deformity. Although previous reports have demonstrated an association between perioperative outcomes and the extent of correction and fusion (number of posterior levels fused, pelvic fixation, combined anterior-posterior fusion), no study has looked at the independent effects of the surgical invasiveness after controlling for operative time. Methods: All adult patients, undergoing posterior spinal fusion for spinal deformity, were identified in the 2010 to 2014 National Surgical Quality Improvement Program (NSQIP) database. Multivariate analysis was used to determine the independent effects of longer operative timing and the surgical invasiveness (number of levels fused, anterior or transforaminal interbody fusions, osteotomies, and pelvic fixation) on 30-day complications. Results: A total of 1540 patients undergoing posterior spinal fusion for adult spinal deformity were identified. The overall rate of complications was 15.3%. In multivariate analysis, greater operative timing was associated with increased inpatient complications [odds ratio (95% confidence interval, 95% CI) from 2.23 (1.25–3.98) for 7–8 hours to 4.46 (2.61–7.64) for 9+ hours; P < 0.001]. Although the number of levels fused, anterior/interbody fusions, osteotomies, and pelvic fixation were associated with complications on bivariate analysis, these factors were not associated with increased complications in multivariate analysis when controlling for other factors such as operative time. Conclusion: For adult deformity surgery, longer operative time appears to be a better predictor of the overall rate perioperative complications than surgical invasiveness in multivariate analysis. Rather than avoidance of a more extensive and invasive surgical procedure, which may be indicated to improve alignment and stability, these data suggest the importance of safely and efficiently minimizing overall operative time. Level of Evidence: 4